Hand grip strength: evaluation methods and factors influencing this measure - Jonathan Ache Dias; Angélica Cristiane Ovando; Wladymir Külkamp; Noe Gomes Borges JR (Universidade Federal de Santa Catarina, 2010)
The evaluation of hand grip strength (HGS) is commonly used, especially in physiotherapy and sports. The establishment of reference values has been the focus of some studies, but the different instruments and protocols used impair generalization of the results. Moreover, several factors influence HGS, such as gender, age, dominance, time of assessment, body position, sincerity of effort, anthropometric characteristics, and grip span. The objective of this study was to review the current state of the art regarding HGS measures and some aspects related to their interpretation. According to the literature, the use of a dynamometer that allows the construction of force vs. time curves and the continuous adjustment of grip span according to hand dimensions seems to be essential for the evaluation of HGS. Additional recommenda-tions are the standardization of the time of evaluation, assessment of both hands, a minimum number of three trials for each hand, adoption of a standard body position, use of verbal and/or visual encouragement, and the correction of muscle strength according to body weight. The standardization of evaluation methods and interpretation of the results permits the establishment of reliable and universally accepted reference values of HGS.